Triiodothyronine levels in athyreotic pediatric patients during levothyroxine therapy - Baran, Julia; Isaza, Amber; Bojarsky, Mya; Alzoebie, Lama; Song, Minkeun; Halada, Stephen; Sisko, Lindsay; Gonzales, Stephanie; Mostoufi-Moab, Sogol; Bauer, Andrew J. (Frontiers in Endocrinology, 2024)
Objective: Levothyroxine (LT4) monotherapy is the current recommended approach for treating pediatric patients post-total thyroidectomy (TT) based on the assumption that peripheral conversion of thyroxine (T4) to triiodothyronine (T3) normalizes thyroid hormone levels. In adults, approximately 15% of post-TT patients on LT4 monotherapy have altered T4:T3 ratios with ongoing debate in regard to the clinical impact with respect to health-related quality of life (hrQOL). The ability to normalize T3 and T4 levels on LT4 monotherapy for pediatric patients’ post-TT is important but not previously described. This study reports data on T3 levels in athyreotic pediatric patients to determine if a similar cohort of patients exists on LT4 monotherapy targeting normalization of TSH (LT4 replacement) or suppression (LT4 suppression). Methods: Thyroid function tests (TFTs) were retrospectively extracted from medical charts for patients <19 years old who underwent TT for definitive treatment of Graves’ disease (GD) or differentiated thyroid cancer (DTC) between 2010-2021. LT4 dosing was selected to normalize the TSH in GD patients (LT4 replacement) or suppress TSH in DTC patients (LT4 suppression). Pre- and post-surgical TSH, T3 and T4 levels were compared. Results: Of 108 patients on LT4 replacement (n=53) or LT4 suppression (n=55) therapy, 94% (102/108) of patients demonstrated T3 levels in the normal range post-TT. However, the majority of patients on LT4 replacement (44/53; 83%) and LT4 suppression (31/55; 56%) displayed post-TT T3 levels in the lower half of the normal range despite 50% (22/44) and 48% (15/31) of these patients, respectively, having post-TT fT4 levels above the upper limit of the normal range. Conclusions: A significant number of pediatric patients do not achieve similar T3 and T4:T3 levels pre- and post-TT. Future multi-center, prospective studies evaluating LT4 monotherapy in comparison to combined LT4/LT3 therapy are warranted to determine the potential clinical impact of altered T3 levels in athyreotic pediatric patients.